Immunohistological screening in the selection of monoclonal antibodies: the use of isotype-specific antiglobulins. - Aqel, N; Clark, M; Cobbold, S; Waldmann, H (1984)
This paper describes the use of the immunoperoxidase technique for the screening of rat hybridoma culture supernatants on tissue sections. By combining the avidin-biotin system with mouse monoclonal antibodies specific to different rat immunoglobulin isotypes, it is possible to resolve the specificity patterns of complex mixtures of monoclonal antibodies from uncloned culture wells. This strategy is particularly useful in the derivation of monoclonal antibodies to cell surface antigens.